2021
DOI: 10.1111/jocn.15908
|View full text |Cite
|
Sign up to set email alerts
|

Medication calculation skills of graduating nursing students within European context

Abstract: Aim:The aim of this study is to evaluate the medication calculation skills of graduating nursing students in six European countries and analyse the associated factors.Background: Medication calculation skills are fundamental to medication safety, which is a substantial part of patient safety. Previous studies have raised concerns about the medication calculation skills of nurses and nursing students.Design: As part of a broader research project, this study applies a multinational crosssectional survey design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…16 This is rendered as a key component in the safe and accurate prescription and administration of drugs and is a prerequisite for accurate drug calculations. 17 Correct drug calculation is a challenge for not only nursing students but also for nurses who face difficulty performing some mathematical and clinical calculations of drugs. 18 According to research, nursing students are prone to failures in drug dose calculations, 15,19 and they experience anxiety when performing mathematical calculations.…”
Section: Methodsmentioning
confidence: 99%
“…16 This is rendered as a key component in the safe and accurate prescription and administration of drugs and is a prerequisite for accurate drug calculations. 17 Correct drug calculation is a challenge for not only nursing students but also for nurses who face difficulty performing some mathematical and clinical calculations of drugs. 18 According to research, nursing students are prone to failures in drug dose calculations, 15,19 and they experience anxiety when performing mathematical calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Mastery of medication calculation skills is one of the tasks nursing students should achieve during their education [12]. Outcome measures, however, indicate that for many students, accurate medication calculations are challenging to both learn and master [13][14][15]. For example, in a European study including six countries, the authors found that even simple calculation tasks were challenging to master correctly for nursing students [15].…”
Section: Introduction 11 Learning and Development Of Professional Com...mentioning
confidence: 99%
“…Outcome measures, however, indicate that for many students, accurate medication calculations are challenging to both learn and master [13][14][15]. For example, in a European study including six countries, the authors found that even simple calculation tasks were challenging to master correctly for nursing students [15]. Medication calculation skills should be acknowledged as a well-defined competency in nursing education curricula and continuing education programs [6,12,16].…”
Section: Introduction 11 Learning and Development Of Professional Com...mentioning
confidence: 99%
“…Research focusing on nursing students suggests they often have poor drug calculation skills, due especially to difficulties with understanding mathematical principles [ 4 ]. Accordingly, although they are usually able to perform simple calculations, they struggle with tasks involving multiple steps and which require a higher level of conceptual knowledge [ 5 ]. A further issue concerns the extent to which nursing students are aware of their errors.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue to consider, and one highlighted in a recent comparative study of six European countries [ 5 ], concerns cross-national differences in medication education regulations and practices and the competences that graduating nurses are expected to have acquired. For instance, some professional bodies such as the UK Nursing & Midwifery Council recommend that nurse education institutions should require students to achieve a 100% pass on a health numeracy assessment including calculation of medicines [ 14 ].…”
Section: Introductionmentioning
confidence: 99%